45. EVALUATION OF THE PERFORMANCE OF THE STROKE UNIT - THONG THAT HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
The Stroke Unit of Thong Nhat Hospital was established in 2014. From 2014 to 2024, under the leadership of the Board of Directors, the stroke unit coordinated with relevant departments to gradually establish and update stroke care protocols including reperfusion treatment for acute ischemic stroke, secondary prevention treatment, and post-stroke care and rehabilitation. Along with participating in the RES-Q registry study, we have applied specific solutions to improve the performance of stroke treatment with the ultimate goal of ensuring that as many patients as possible can get benefit from these advancements. Our stroke unit was honored to receive Gold Status Award from The World Stroke Organization for stroke treatment performance in 2020, then Platinum Status Award in 2023 and finally Diamond Status Award in 1st quarter of 2024.
Keywords: stroke unit; acute stroke; ischemic stroke; secondary prevention; RES-Q